ChemInform Abstract: Palmaerins A—D, New Chlorinated and Brominated Dihydroisocoumarins with Antimicrobial and Plant Growth Regulating Activities from Discomycete Lachnum palmae. Issue 44 (14th October 2013) - Tanabe, Yuka; Matsumoto, Takunori; Hosoya, Tsuyoshi; Sato, Hiroyasu; Shigemori, Hideyuki
Abstract Palmaerins A‐C (Ia)—(Ic) show antimicrobial activity against Bacillus subtilus and Staphylococcus aureus, whilst antifungal activity against Penicillium sp.